A Population Pharmacokinetic Model Incorporating Saturable Pharmacokinetics and Autoinduction for High Rifampicin Doses - Svensson, Robin J.; Aarnoutse, Rob E.; Diacon, Andreas H.; Dawson, Rodney; Gillespie, Stephen H.; Boeree, Martin J.; Simonsson, Ulrika S.H. (Clinical pharmacology and therapeutics, 2018)
Accumulating evidence suggests that increasing doses of rifampicin may shorten tuberculosis treatment. The PanACEA HIGHRIF1 trial assessed safety, pharmacokinetics, and antimycobacterial activity of rifampicin at doses up to 40 mg/kg. Eighty‐three pulmonary tuberculosis patients received 10, 20, 25, 30, 35, or 40 mg/kg rifampicin daily over 2 weeks, supplemented with standard doses of isoniazid, pyrazinamide, and ethambutol in the second week. This study aimed at characterizing rifampicin pharmacokinetics observed in HIGHRIF1 using nonlinear mixed effects modeling. The final population pharmacokinetic model included an enzyme turnover model accounting for time‐dependent elimination due to autoinduction, concentration‐dependent clearance, and dose‐dependent bioavailability. The relationship between clearance and concentration was characterized by a Michaelis–Menten relationship. The relationship between bioavailability and dose was described using an Emax relationship. The model will be key in determining exposure–response relationships for rifampicin and should be considered when designing future trials and when treating future patients with high‐dose rifampicin.